Draft Eighth Five Year Plan 1990-95 and Annual Plan 1991-92 - Planning Commission, Government of India (Planning Commission, Government of India, 1990)
A welcome present for the nineties of Delhi will be a realistic, long sustaining and growth oriented Eighth Five Year Plan. It all the more so because an objective assessment of increasing realities of a monolithic city structure of almost a mini State size is increasingly lending credence to the concept that planning is not merely a development process but a way of life as well. A pragmatic plan formulation is essentially a step forward to ultimate plan success inextricably linked with the cohesiveness of city's overall life pattern.
Planning Department Delhi Administration
Planning Department Delhi Administration
Keywords: Eighth Five Year Plan- India; Economic and Social Development